Identifikasi Risiko Keselamatan dan Penanganan Overhaul Auxiliary Engine di Atas Kapal MT.Pasaman - Octavianus Bungalangan; Frisca Mareyta Pongoh; Aliong Silalahi (KALAO'S MARITIME JOURNAL, 2024)
Safety Risk Identification and Handling of Auxiliary Engine Overhaul on Ship is a process that aims to identify potential risks and hazards associated with repairing or maintaining auxiliary engines on ships, as well as developing appropriate handling strategies to mitigate those risks. Safety Risk Identification is carried out with several things, namely Safety Analysis, Hazard Identification, Risk Evaluation, Risk Classification. The handling that can be done in the axuliary egine overhaul is Planning, Education and Training, Use of Equipment and Technology, Supervision and Control, Evaluation and Repair. By identifying safety risks and implementing appropriate handling strategies, vessels can minimize the potential for accidents and injuries during the auxiliary engine overhaul process. This not only protects the ship's crew but also ensures the smooth operation of the ship overall. This study adopts a qualitative approach, conducted through verbal interviews with engine crews and direct observation during the implementation on board. The findings of the study show that safety risks and handling of auxiliary egine overhaul on ships are essential for identifying and maintaining repairs to ship engines.